Pelvic organ prolapse: Does the postoperative course of mesh-repair surgery differ in elderly women when compared with younger patients? - Rzepka, Jakub; Brocker, Kerstin A.; Alt, Christina; Corteville, Caroline; Sohn, Christof; Lenz, Florian (Journal of obstetrics and gynaecology, 2010)
Pelvic organ prolapse (POP) is a common disease in elderly women. Among a wide range of possibilities in POP surgery, the use of partially absorbable meshes appears to be very promising. The problem concerning POP therapy in elderly patients has not yet been not sufficiently investigated. We enrolled 64 patients with POP stages 3 and 4. All patients underwent mesh-repair surgery and afterwards were stratified into two age groups. Data obtained from anamnesis, pelvic organ prolapse quantification (POP-Q) scale, dynamic MRI and prolapse quality of life (P-QoL) questionnaire were analysed and compared between both age groups. A total of 64 patients completed the study protocol. Outcome of the surgery was promising and comparable between both age groups. One recurrence of prolapse and one mesh erosion was reported. P-QoL showed a good overall satisfaction. Our data show that the surgical correction of POP with use of polypropylene mesh in elderly women appears to be a successful method with an acceptable morbidity, adverse events rate and high satisfaction of the patients.